Psychometric evidence of the Woman Abuse Screening Tool in Peruvian women victims and non-victims of intimate partner violence - Domínguez-Vergara, Julio (2025)
Objective: the present study evaluated the factorial validity, measurement invariance, reliability and graded response model of the WAST in a sample of female victims and non-victims of intimate partner violence. Method: A total of 285 Peruvian women participated (59.6% were victims of intimate partner violence and 40.4% were not victims of intimate partner violence), with ages ranging from 18 to 64 years and an average age of 31.73 years for victims of intimate partner violence and 26.54 years for non-victims. The confirmatory factor analysis (CFA) suggested a twofactor model that was significantly adjusted for the group of female victims of IPV and non-victims of IPV. Results: The multigroup CFA supported factorial invariance according to female IPV and non-IPV victims of the WAST. Reliability was adequate and was calculated using the omega coefficient. Finally, the WAST items showed adequate discrimination indexes and a correct ordering of the difficulty thresholds. Conclusion: The results showed that the WAST possesses good evidence of validity, reliability, invariance and graded response model in women victims and non-victims of IPV.